Улаанбаатар орчмын байгалийн гэрэлтүүлгийн судалгааны үр дүн - О., Энхнасан; Ц., Баатарчулуун; Г., Батсүх (Scientific transaction of the National University of Mongolia. Physics, 2022)
The trends of total and diffuse natural illumination have been determined at Ulaanbaatar city by using the measurements with the BGBB-2 instrument during last 10 years. Results of the mean daily course of total and diffuse natural illumination for each season, the dependence of natural illumination on the solar elevation angle and the yearly trend of natural illumination have been presented in this paper.